Complementary Effects of Species Abundances and Ecological Neighborhood on the Occurrence of Fruit-Frugivore Interactions - Donoso, Isabel; García, Daniel; Martínez, Daniel; Tylianakis, Jason M.; Stouffer, Daniel B. (Frontiers in Ecology and Evolution, 2017)
Species interactions are traditionally seen as the outcome of both ecological and evolutionary mechanisms. Among them, the two most frequently studied are the neutral role of species abundances in determining encounter probability and the deterministic role of species identity (traits and evolutionary history) in determining the compatibility of interacting. Nevertheless, the occurrence of pairwise interactions also depends on the spatio-temporal context imposed by the ecological neighborhood (i.e. the indirect effect of other local species sharing traits and interaction potential with the focal ones). Although a few studies have begun to examine neighborhood effects on community interactions, these have not incorporated neighborhood structure as a complementary driver of pairwise interactions within an integrative approach. Here we describe the spatial structure of pairwise interactions between three fleshy-fruited tree species and six frugivorous thrush species within the same locality of the Cantabrian Range (Iberian Peninsula). Using a spatio-temporally fine-grained dataset sampled during three years, we aimed to detect spatial patterns of interactions and to evaluate their concordance across years. We also evaluated the simultaneous roles played by species abundance, species identity and the ecological neighborhood in determining the pairwise interaction frequencies based on fruit removal. Our results showed that the abundances of fruit and bird species involved in plant-frugivore interactions, and the spatial patterns of these interactions, varied among years, and this was mainly due to different fruiting landscapes responding to masting events of distinct plant species. Despite high interannual differences in species abundances and the pairwise interaction frequencies, the main mechanisms underpinning the occurrence of pairwise interactions remained constant. Most of the variability in pairwise interactions was always explained by interacting fruit and bird species’ abundances. Ecological neighborhood, characterized as the net quantity of forest cover, heterospecific fruit crops, and heterospecific bird abundances in the immediate surroundings, also affected pairwise interaction frequency through its indirect effects on the abundance of interacting bird species. Our results highlight the prevalence of neutral forces in highly generalized plant-frugivore assemblages as well as the influence of indirect interactions (competition and/or facilitation with other local species) as another important driver to consider when predicting pairwise interactions.